Method for efficiently and cleanly extracting lithium from low-grade lepidolite
By mixing the auxiliary materials such as lithium cloud mother with sodium and potassium sulfate, and the steps of high -temperature roasting, immersion, and removal, the low -quality lithium cloud mother lithium lifting technology consumes large energy, non -environmental protection, difficulty removal, high processing costs, high processing costs. The problem realizes the efficient extraction and recycling of lithium, reducing production costs and environmental impacts.
Patent Information
- Application Number
- CN202411412340.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing low-grade lithium mica extraction process has problems such as high energy consumption, unenvironmental protection, difficulty in removing impurities and high processing costs.
Sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz and other auxiliary materials are mixed with lithium cloud mother. The steps of high -temperature roasting, leaching, removing, and lithium sinks are used to achieve the efficient extraction and recycling of lithium.
It has improved the conversion rate and total recovery rate of lithium, reduced production costs and environmental impacts, and achieved the economic, efficient and environmental protection goals of the process.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a method for efficiently and cleanly extracting lithium from low-grade lepidolite. Background Art
[0002] Lithium and its compounds are indispensable materials for modern industry and have important applications in the fields of batteries, ceramics, lubricants, etc. Although my country has rich lithium resources, most of them are found in salt lake brine. Limited by resource endowment, geographical location and climate, its production capacity is far from meeting the needs of the rapid development of the new energy industry. Lithium extraction from ore has become an important source of lithium products. The development and utilization of lithium mica resources is of great significance to ensure the sustainable development of lithium resources. At present, lithium mica in some areas is generally "poor, fine and mixed", which makes us have to face the use of low-grade lithium mica for lithium extraction. The main lithium extraction processes of lithium mica include limestone roasting, chloride roasting, sulfate roasting, sulfuric acid leaching and pressure leaching.
[0003] When lithium is extracted from existing low-grade lithium mica, the limestone method requires three times the amount of limestone as the lithium mica, which consumes a lot of energy and produces a large amount of slag; the chlorination roasting method causes serious corrosion to the equipment and is not conducive to environmental protection; the sulfuric acid leaching method is relatively mature, but there are problems such as difficulty in removing impurities from the leachate and equipment corrosion; the sulfate method is currently the most mainstream process, which basically produces lithium carbonate through the process of "roasting-leaching-impurity removal-precipitation-washing-filtration", but the main auxiliary materials used are potassium sulfate, calcium sulfate, etc., which are relatively expensive. Therefore, it is necessary to develop an economical, efficient, environmentally friendly, and high comprehensive recovery rate lithium extraction process. To this end, we propose a method for efficient and clean lithium extraction from low-grade lithium mica. Summary of the invention
[0004] The purpose of the present invention is to provide a method for efficiently and cleanly extracting lithium from low-grade lepidolite, so as to solve the problems of high energy consumption, environmental pollution, difficulty in impurity removal and high processing cost in the existing low-grade lepidolite lithium extraction method mentioned in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for efficiently and cleanly extracting lithium from low-grade lepidolite, comprising the following steps:
[0006] S1: Mixing lepidolite with sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz, and then pressing the mixed raw materials into bricks;
[0007] S2, stacking, preheating and drying, high-temperature roasting, cooling, crushing and grinding the bricks to obtain fine powder clinker;
[0008] S3: the fine powder clinker is leached with water, and then a leaching liquid is obtained by solid-liquid separation;
[0009] S4: The leachate is subjected to impurity removal, concentration, lithium precipitation, and centrifugal separation to obtain crude lithium carbonate and mother liquor after lithium precipitation, and then the crude lithium carbonate is stirred, washed, dried, and crushed to obtain battery-grade lithium carbonate;
[0010] S5: The mother liquor after lithium precipitation is decarbonized, neutralized and concentrated to obtain recovered sodium potassium sulfate and concentrated mother liquor, and then the sodium potassium sulfate is recovered and returned to S1 for mixing, and the concentrated mother liquor is returned to S4.
[0011] It is convenient to accelerate the solid phase reconstruction reaction of lithium mica by adopting sodium sulfate potassium salt, thereby improving the conversion rate of lithium; on the other hand, by adding quartz, the solid phase reaction free energy of lithium mica and sulfate can be effectively reduced, so that low-grade lithium mica can also have a good transformation rate; adding lime and calcium hydroxide is significantly better than adding calcium carbonate, which can not only effectively absorb the HF gas produced by the reaction, but also avoid reducing the leaching of lithium due to the combination of fluorine and lithium, which is beneficial to improving the leaching rate of lithium, but also effectively absorb SO2 and SO3 produced in the roasting process, reduce the pressure of tail gas treatment, and benefit environmental protection; adding lime can effectively increase the melting point of sodium sulfate, and prevent the formation of glass in the reaction above 880°C, which leads to a decrease in the transformation rate.
[0012] Preferably, in S1, the mass ratio of lepidolite to sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz on a dry basis is 100:(10-15):(30-35):(3-5):(3-5):(2-4).
[0013] It is convenient to increase the lithium leaching rate through appropriate matching.
[0014] Preferably, in S1: the lithium oxide grade of the lepidolite ore is 1.8-2.0%.
[0015] It is convenient to extract lithium from low-grade lithium mica ore.
[0016] Preferably, in S1: the main content of calcium oxide in the lime is ≥80%, and the main content of silicon dioxide in the quartz is ≥90%.
[0017] It is convenient to absorb the HF gas produced by the reaction, and can avoid reducing the leaching of lithium due to the combination of fluorine and lithium.
[0018] Preferably, in S1: the bricks are pressed into green bricks by a hydraulic brick-making machine, and the green bricks have a compressive strength of 23-25 MPa.
[0019] It is convenient to make the contact between lithium mica and auxiliary materials more complete, which is beneficial to solid phase reaction. In addition, the use of tunnel kiln baking can accurately control the reaction temperature and reaction time to ensure that the bricks are burned into mature materials, thereby improving the transformation rate.
[0020] Preferably, in S2, the high temperature calcination temperature is 900-950°C, and the calcination time is 60-120 min.
[0021] It is convenient to ensure the transformation rate and total recovery rate of clinker lithium through appropriate roasting time.
[0022] Preferably, in S2: the particle size of the fine powder clinker is controlled to be more than 95% at -100 mesh.
[0023] Facilitates better contact area and improves leaching effect.
[0024] Preferably, in said S3: water immersion, the liquid-to-solid ratio is controlled to be (1.2-1.5):1, the leaching time is 30-50 min, and the leaching temperature is 50°C-80°C.
[0025] Preferably, in S4: the lithium precipitation reaction temperature is 90-95°C.
[0026] It is convenient to precipitate lithium through lithium precipitation reaction, and obtain crude lithium carbonate and mother liquor after lithium precipitation by centrifugal separation.
[0027] Preferably, in S5: after lithium precipitation, the mother liquor is decarbonized with sulfuric acid to a pH of 5.5-6.5, and then neutralized with sodium hydroxide to a pH of 7.5-8.5.
[0028] It is convenient to decarbonize the mother liquor after lithium precipitation and adjust the pH value to achieve neutralization.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention uses sodium sulfate potassium salt, which contains 8-12% potassium sulfate, to accelerate the solid phase reconstruction reaction of lithium mica, thereby improving the conversion rate of lithium; on the other hand, by adding quartz, the solid phase reaction free energy of lithium mica and sulfate can be effectively reduced, so that low-grade lithium mica can also have a good transformation rate; adding lime and calcium hydroxide is significantly better than adding calcium carbonate, which can not only effectively absorb the HF gas generated by the reaction, but also avoid reducing the leaching of lithium due to the combination of fluorine and lithium, which is beneficial to improving the leaching rate of lithium, but also effectively absorb SO2 and SO3 generated in the roasting process, reduce the tail gas treatment pressure, and benefit environmental protection; adding lime can effectively increase the melting point of sodium sulfate, and prevent the formation of glassy state in the reaction above 880°C, which leads to a decrease in the transformation rate.
[0031] (2) The present invention adopts the method of pressing bricks before entering into a tunnel kiln for firing. Pressing bricks can make the contact between lithium mica and auxiliary materials more complete, which is beneficial to the solid phase reaction. In addition, the use of a tunnel kiln for firing can accurately control the reaction temperature and reaction time, ensuring that the bricks are fired into mature materials, thereby improving the transformation rate.
[0032] (3) The amount of sodium potassium sulfate recovered by the present invention is substantially equal to the amount of sodium potassium sulfate used in the mixing, thereby achieving material recycling, being more environmentally friendly and energy-saving, and saving production costs. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] The present invention provides a technical solution: a method for efficiently and cleanly extracting lithium from low-grade lepidolite, comprising the following steps:
[0036] S1: Mixing lepidolite with sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz, and then pressing the mixed raw materials into bricks, wherein the sodium potassium sulfate contains 8-12% potassium sulfate;
[0037] S2, stacking, preheating and drying, high-temperature roasting, cooling, crushing and grinding the bricks to obtain fine powder clinker;
[0038] S3: The fine powder clinker is leached with water, and then a leaching solution is obtained by solid-liquid separation;
[0039] S4: The leachate is subjected to impurity removal, concentration, lithium precipitation, and centrifugal separation to obtain crude lithium carbonate and mother liquor after lithium precipitation, and then the crude lithium carbonate is further stirred, washed, dried, and crushed to obtain battery-grade lithium carbonate, so as to ensure the effect of lithium extraction by impurity removal and reduce the influence of impurities;
[0040] S5: After lithium precipitation, the mother liquor is decarbonized, neutralized and concentrated to obtain recovered sodium potassium sulfate and concentrated mother liquor. The recovered sodium potassium sulfate is then returned to S1 for mixing, and the concentrated mother liquor is returned to S4.
[0041] The leachate in S4 is firstly added with lime to remove iron, and the pH is controlled to be 7.5-8.5 to obtain a primary purified liquid, and then soda ash is added to the primary purified liquid to remove impurities, and the added amount is 105-110% of the theoretical value of converting calcium and magnesium ions in the solution into calcium carbonate and magnesium carbonate. After stirring and filtering, secondary impurity removal slag and secondary purified liquid are obtained. The secondary purified liquid first enters MVR to be concentrated to a lithium oxide concentration of 28-30g / L, and then is deeply filtered through resin to remove calcium and magnesium to obtain a purified liquid, and a soda ash solution is added to the purified liquid, and the amount of soda ash used is 105-115% of the theoretical value of sodium carbonate required to convert all lithium ions in the solution into lithium carbonate.
[0042] Preferably, in S1, the mass ratio of lepidolite ore to sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz on a dry basis is 100:(10-15):(30-35):(3-5):(3-5):(2-4).
[0043] Preferably, in S1: the lithium oxide grade of the lepidolite ore is 1.8-2.0%.
[0044] Preferably, in S1: the main content of calcium oxide in the lime is ≥80%, and the main content of silicon dioxide in the quartz is ≥90%.
[0045] Preferably, in S1: the bricks are pressed into green bricks by a hydraulic brick making machine, and the green bricks have a compressive strength of 23-25 MPa.
[0046] Preferably, in S2: the temperature of high temperature roasting is 900-950°C, the roasting time is 60-120min, and the preheating and drying in S3 uses the residual heat of high temperature roasting for drying.
[0047] Preferably, in S2: the particle size of the fine powder clinker is controlled to be more than 95% at -100 mesh.
[0048] Preferably, in S3: water immersion, the liquid-to-solid ratio is controlled to be (1.2-1.5):1, the leaching time is 30-50min, the leaching temperature is 50°C-80°C, the filter residue is repeatedly washed with water twice, the filter residue is repeatedly washed with circulating water twice, the filtrate from the washing residue is returned step by step, and the lithium oxide content of the leaching solution is guaranteed to be 15-20g / L.
[0049] Preferably, in S4: the lithium precipitation reaction temperature is 90-95°C, the reaction time is 2-3h, and crude lithium carbonate is obtained by centrifugation. The crude lithium carbonate is then washed with pure water at a solid-liquid ratio of 1:3-4 at above 90°C for 30-60min, centrifuged, dried, and crushed to obtain battery-grade lithium carbonate, and the washing water is used to prepare a soda ash solution.
[0050] Preferably, in S5: after lithium precipitation, the mother liquor is decarbonized with sulfuric acid to a pH of 5.5-6.5, and then neutralized with sodium hydroxide to a pH of 7.5-8.5, and the neutralization reaction end point pH is controlled to be 7.5-8.5, the decarbonized mother liquor is concentrated by MVR and then centrifuged to obtain sodium potassium sulfate, which is used for mixing in S1, and the amount of sodium potassium sulfate produced is balanced with the amount of sodium potassium sulfate used in S1, so as to realize material circulation, and the mother liquor is evaporated and the operation of S4 is repeated.
[0051] Example 2
[0052] The present invention provides a technical solution: a method for efficiently and cleanly extracting lithium from low-grade lepidolite, comprising the following steps:
[0053] S1. The lithium oxide grade of 2.0% lepidolite is mixed in a mass ratio of 100:13:30:4:3:3 of lepidolite: sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz to obtain a mixed raw material. The mixed raw material is pressed into a brick by a hydraulic brick press, and the compressive strength of the brick is controlled to be 23.5 MPa.
[0054] S2, stacking the bricks of S1, entering the preheating and drying tunnel kiln through the kiln car for drying, transferring to the firing tunnel kiln for high-temperature roasting, controlling the roasting temperature to 920°C, the high-temperature roasting time to 70min, obtaining the burnt clinker, and then cooling in the cooling kiln for crushing, transferring to the vertical mill for grinding, controlling the grinding particle size to -100 mesh to account for 95%, obtaining fine powder clinker;
[0055] S3. Add the fine powder clinker obtained in S2 into the slag washing filtrate for leaching, control the liquid-solid ratio to 1.2:1, stir and leaching for 30 minutes, filter to obtain the leachate, wash the filter residue with circulating water for 2 times, return the slag washing filtrate step by step, and ensure that the lithium oxide content of the leachate is 15-20g / L.
[0056] S4, the leaching solution of S3 is first added with lime to remove iron, the pH is controlled to 8-9, and filtered to obtain a primary purified liquid and a primary purified slag; the primary purified liquid is then added with soda ash to remove impurities, and the added amount is 105-110% of the theoretical value of calcium and magnesium ions in the solution to convert them into calcium carbonate and magnesium carbonate, and stirred and filtered to obtain secondary impurity removal slag and secondary purified liquid; the secondary purified liquid is then concentrated by MVR to a lithium oxide concentration of 28-30g / L to obtain a lithium sulfate concentrated solution, and the concentrated solution is filtered by resin to deeply remove calcium and magnesium to obtain a purified finished liquid; the net Add a soda ash solution to the finished solution, the amount of soda ash used is 105-115% of the theoretical value of sodium carbonate required to convert all lithium ions in the solution into lithium carbonate, the lithium precipitation reaction temperature is controlled at 95°C, the reaction time is 2h, centrifugal separation is performed to obtain crude lithium carbonate and mother liquor after lithium precipitation, the crude lithium carbonate is then added with pure water at a solid-liquid ratio of 1:4 at 90°C and stirred and washed twice, the stirring and washing time is 40min, centrifugal separation is performed to obtain second-washed lithium carbonate, the second-washed lithium carbonate is dried and then air flow pulverized to obtain battery-grade lithium carbonate, and the first washing water is used to prepare a soda ash solution;
[0057] S5, the mother liquor after lithium precipitation obtained in S4 is added with concentrated sulfuric acid for decarbonization, and the pH value of the reaction endpoint is controlled to be 5.5-6.5. The decarbonized mother liquor is then neutralized by adding sodium hydroxide, and the pH value of the reaction endpoint is controlled to be 7.5-8.5. The neutralized mother liquor is concentrated by MVR and then centrifuged to obtain sodium sulfate potassium salt and concentrated mother liquor. The sodium sulfate potassium salt is returned to S1 for mixing, and the amount of sodium sulfate potassium salt produced is balanced with the amount of sodium sulfate potassium salt used in S1, so as to realize material circulation, and the concentrated mother liquor repeats the operation of S4;
[0058] Take S2 clinker to test the transformation rate and the lithium oxide grade of leached slag. The calculation method of the transformation rate is as follows:
[0059]
[0060] According to the test, the conversion rate of clinker lithium in the above method is 89.7%, and the total lithium recovery rate is 76.3%.
[0061] Example 3
[0062] The present invention provides a technical solution: a method for efficiently and cleanly extracting lithium from low-grade lepidolite, comprising the following steps:
[0063] S1. Fully mix the lithium mica ore with a lithium oxide grade of 1.95% according to the mass ratio of lithium mica: sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz of 100:15:30:3:4:3 to obtain a mixed raw material, and press the mixed raw material into a brick by a hydraulic brick press, and control the compressive strength of the brick to be 24Mpa;
[0064] S2, stacking the bricks of S1, entering the preheating and drying tunnel kiln for drying through a kiln car, transferring to the firing tunnel kiln for high-temperature roasting, controlling the roasting temperature to 930°C, and the high-temperature roasting time to 80min, to obtain the burnt clinker, and then cooling in a cooling kiln for crushing, transferring to a vertical mill for grinding, controlling the grinding particle size to -100 mesh to account for 95%, to obtain fine powder clinker;
[0065] S3. Add the fine powder clinker obtained in S2 into the slag washing filtrate for leaching, control the liquid-solid ratio to 1.2:1, stir and leaching for 30 minutes, filter to obtain the leachate, wash the filter residue with circulating water for 2 times, return the slag washing filtrate step by step, and ensure that the lithium oxide content of the leachate is 15-20g / L.
[0066] S4, first add lime to the leachate to remove iron, control the pH to 8-9, filter to obtain a primary purified liquid and a primary purified slag; then add soda ash to the primary purified liquid to remove impurities, the amount added is 105-110% of the theoretical value of calcium and magnesium ions in the solution to convert them into calcium carbonate and magnesium carbonate, stir and filter to obtain secondary impurity removal slag and secondary purified liquid; the secondary purified liquid is then concentrated by MVR to a lithium oxide concentration of 28-30g / L to obtain a lithium sulfate concentrate, the concentrate is filtered by resin to deeply remove calcium and magnesium to obtain a purified liquid; the purified liquid Add a soda ash solution to the solution, the amount of soda ash used is 105-115% of the theoretical value of sodium carbonate required to convert all lithium ions in the solution into lithium carbonate, the lithium precipitation reaction temperature is controlled at 95°C, the reaction time is 2h, centrifugal separation is performed to obtain crude lithium carbonate and mother liquor after lithium precipitation, the crude lithium carbonate is then added with pure water at a solid-liquid ratio of 1:4 at 90°C and stirred and washed twice, the stirring and washing time is 40min, centrifugal separation is performed to obtain second-washed lithium carbonate, the second-washed lithium carbonate is dried and then air flow pulverized to obtain battery-grade lithium carbonate, and the first washing water is used to prepare a soda ash solution;
[0067] S5, after lithium precipitation, the mother liquor is added with concentrated sulfuric acid for decarbonization, and the pH value at the reaction end point is controlled to be 5.5-6.5. The decarbonized mother liquor is then neutralized with sodium hydroxide, and the pH value at the reaction end point is controlled to be 7.5-8.5. The neutralized mother liquor is concentrated by MVR and then centrifuged to obtain sodium sulfate potassium salt and the concentrated mother liquor. The sodium sulfate potassium salt is returned to S1 for mixing, and the amount of sodium sulfate potassium salt produced is balanced with the amount of sodium sulfate potassium salt used in S1, so as to realize material circulation, and the concentrated mother liquor repeats the operation of S4;
[0068] Take S2 clinker to test the transformation rate and the lithium oxide grade of leached slag. The calculation method of the transformation rate is as follows:
[0069]
[0070] According to the test, the conversion rate of clinker lithium in the above method is 88.96%, and the total lithium recovery rate is 75.82%.
[0071] Example 4
[0072] The present invention provides a technical solution: a method for efficiently and cleanly extracting lithium from low-grade lepidolite, comprising the following steps:
[0073] S1. Fully mix the lithium mica ore with a lithium oxide grade of 1.9% according to the mass ratio of lithium mica: sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz of 100:15:31:4:4:3 to obtain a mixed raw material, and press the mixed raw material into a brick by a hydraulic brick press, and control the compressive strength of the brick to be 24Mpa;
[0074] S2, stacking the bricks of S1, entering the preheating and drying tunnel kiln through the kiln car for drying, transferring to the firing tunnel kiln for high-temperature roasting, controlling the roasting temperature to 950°C, the high-temperature roasting time to 90min, obtaining the burnt clinker, and then cooling in the cooling kiln for crushing, transferring to the vertical mill for grinding, controlling the grinding particle size to -100 mesh to account for 95%, obtaining the fine powder clinker;
[0075] S3. Add the fine powder clinker obtained in S2 into the slag washing filtrate for leaching, control the liquid-solid ratio to 1.3:1, stir and leaching for 30 minutes, filter to obtain the leaching solution, wash the filter residue with circulating water for 2 times, return the slag washing filtrate step by step, and ensure that the lithium oxide content of the leaching solution is 15-20g / L.
[0076] S4, first add lime to the leachate to remove iron, control the pH to 8-9, filter to obtain a primary purified liquid and a primary purified slag; then add soda ash to the primary purified liquid to remove impurities, the amount added is 105-110% of the theoretical value of calcium and magnesium ions in the solution to convert them into calcium carbonate and magnesium carbonate, stir and filter to obtain secondary impurity removal slag and secondary purified liquid; the secondary purified liquid is then concentrated by MVR to a lithium oxide concentration of 28-30g / L to obtain a lithium sulfate concentrate, the concentrate is filtered by resin to deeply remove calcium and magnesium to obtain a purified liquid; the purified liquid Add a soda ash solution to the solution, the amount of soda ash used is 105-115% of the theoretical value of sodium carbonate required to convert all lithium ions in the solution into lithium carbonate, the lithium precipitation reaction temperature is controlled at 95°C, the reaction time is 2h, centrifugal separation is performed to obtain crude lithium carbonate and mother liquor after lithium precipitation, the crude lithium carbonate is then added with pure water at a solid-liquid ratio of 1:4 at 90°C and stirred and washed twice, the stirring and washing time is 40min, centrifugal separation is performed to obtain second-washed lithium carbonate, the second-washed lithium carbonate is dried and then air flow pulverized to obtain battery-grade lithium carbonate, and the first washing water is used to prepare a soda ash solution;
[0077] S5, after lithium precipitation, the mother liquor is added with concentrated sulfuric acid for decarbonization, and the pH value at the reaction end point is controlled to be 5.5-6.5. The decarbonized mother liquor is then neutralized with sodium hydroxide, and the pH value at the reaction end point is controlled to be 7.5-8.5. The neutralized mother liquor is concentrated by MVR and then centrifuged to obtain sodium sulfate potassium salt and the concentrated mother liquor. The sodium sulfate potassium salt is returned to S1 for mixing, and the amount of sodium sulfate potassium salt produced is balanced with the amount of sodium sulfate potassium salt used in S1, so as to realize material circulation, and the concentrated mother liquor repeats the operation of S4;
[0078] Take S2 clinker to test the transformation rate and the lithium oxide grade of leached slag. The calculation method of the transformation rate is as follows:
[0079]
[0080] According to the test, the conversion rate of clinker lithium in the above method is 90.02%, and the total lithium recovery rate is 77.65%.
[0081] Comparative Example 1
[0082] This comparative example provides a method for efficiently and cleanly extracting lithium from low-grade lepidolite, comprising the following steps:
[0083] S1. The lithium oxide grade of 2.0% lepidolite is mixed in a mass ratio of 100:13:30:4:3:3 of lepidolite: sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz to obtain a mixed raw material. The mixed raw material is pressed into a brick by a hydraulic brick press, and the compressive strength of the brick is controlled to be 23.5 MPa.
[0084] S2, stacking the bricks of S1, entering the preheating and drying tunnel kiln through the kiln car for drying, transferring to the firing tunnel kiln for high-temperature roasting, controlling the roasting temperature to 950°C, the high-temperature roasting time to 70min, obtaining the burnt clinker, and then cooling in the cooling kiln for crushing, transferring to the vertical mill for grinding, controlling the grinding particle size to -100 mesh to account for 95%, obtaining fine powder clinker;
[0085] S3. Add the fine powder clinker obtained in S2 into the slag washing filtrate for leaching, control the liquid-solid ratio to 1.2:1, stir and leaching for 30 minutes, filter to obtain the leachate, wash the filter residue with circulating water for 2 times, return the slag washing filtrate step by step, and ensure that the lithium oxide content of the leachate is 15-20g / L.
[0086] S4, first add lime to the leachate to remove iron, control the pH to 8-9, filter to obtain a primary purified liquid and a primary purified slag; then add soda ash to the primary purified liquid to remove impurities, the added amount is 105-110% of the theoretical value of calcium and magnesium ions in the solution to convert them into calcium carbonate and magnesium carbonate, stir and filter to obtain secondary impurity removal slag and secondary purified liquid; the secondary purified liquid is then concentrated by MVR to a lithium oxide concentration of 28-30g / L to obtain a lithium sulfate concentrate, the concentrate is filtered by resin to deeply remove calcium and magnesium to obtain a purified liquid; the purified liquid Add a soda ash solution to the solution, the amount of soda ash used is 105-115% of the theoretical value of sodium carbonate required to convert all lithium ions in the solution into lithium carbonate, the lithium precipitation reaction temperature is controlled at 95°C, the reaction time is 2h, centrifugal separation is performed to obtain crude lithium carbonate and mother liquor after lithium precipitation, the crude lithium carbonate is then added with pure water at a solid-liquid ratio of 1:4 at 90°C and stirred and washed twice, the stirring and washing time is 40min, centrifugal separation is performed to obtain second-washed lithium carbonate, the second-washed lithium carbonate is dried and then air flow pulverized to obtain battery-grade lithium carbonate, and the first washing water is used to prepare a soda ash solution;
[0087] S5, after lithium precipitation, the mother liquor is added with concentrated sulfuric acid for decarbonization, and the pH value at the reaction end point is controlled to be 5.5-6.5. The decarbonized mother liquor is then neutralized with sodium hydroxide, and the pH value at the reaction end point is controlled to be 7.5-8.5. The neutralized mother liquor is concentrated by MVR and then centrifuged to obtain sodium sulfate potassium salt and the concentrated mother liquor. The sodium sulfate potassium salt is returned to S1 for mixing, and the amount of sodium sulfate potassium salt produced is balanced with the amount of sodium sulfate potassium salt used in S1, so as to realize material circulation, and the concentrated mother liquor repeats the operation of S4;
[0088] Take S2 clinker to test the transformation rate and the lithium oxide grade of leached slag. The calculation method of the transformation rate is as follows:
[0089]
[0090] Compared with Example 2, the calcination temperature was increased from 920°C to 950°C.
[0091] According to the test, the conversion rate of clinker lithium in the above method is 91.32%, and the total recovery rate is 78.08%.
[0092] Comparative Example 2
[0093] This comparative example provides a method for efficiently and cleanly extracting lithium from low-grade lepidolite, comprising the following steps:
[0094] S1. Fully mix the lithium mica ore with a lithium oxide grade of 1.95% according to the mass ratio of lithium mica: sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz of 100:10:30:3:4:3 to obtain a mixed raw material, and press the mixed raw material into a brick by a hydraulic brick press, and control the compressive strength of the brick to be 24Mpa;
[0095] S2, stacking the bricks of S1, entering the preheating and drying tunnel kiln for drying through a kiln car, transferring to the firing tunnel kiln for high-temperature roasting, controlling the roasting temperature to 930°C, and the high-temperature roasting time to 80min, to obtain the burnt clinker, and then cooling in a cooling kiln for crushing, transferring to a vertical mill for grinding, controlling the grinding particle size to -100 mesh to account for 95%, to obtain fine powder clinker;
[0096] S3. Add the fine powder clinker obtained in S2 into the slag washing filtrate for leaching, control the liquid-solid ratio to 1.2:1, stir and leaching for 30 minutes, filter to obtain the leachate, wash the filter residue with circulating water for 2 times, return the slag washing filtrate step by step, and ensure that the lithium oxide content of the leachate is 15-20g / L.
[0097] S4, first add lime to the leachate to remove iron, control the pH to 8-9, filter to obtain a primary purified liquid and a primary purified slag; then add soda ash to the primary purified liquid to remove impurities, the added amount is 105-110% of the theoretical value of calcium and magnesium ions in the solution to convert them into calcium carbonate and magnesium carbonate, stir and filter to obtain secondary impurity removal slag and secondary purified liquid; the secondary purified liquid is then concentrated by MVR to a lithium oxide concentration of 28-30g / L to obtain a lithium sulfate concentrate, the concentrate is filtered by resin to deeply remove calcium and magnesium to obtain a purified liquid; the purified liquid Add a soda ash solution to the solution, the amount of soda ash used is 105-115% of the theoretical value of sodium carbonate required to convert all lithium ions in the solution into lithium carbonate, the lithium precipitation reaction temperature is controlled at 95°C, the reaction time is 2h, centrifugal separation is performed to obtain crude lithium carbonate and mother liquor after lithium precipitation, the crude lithium carbonate is then added with pure water at a solid-liquid ratio of 1:4 at 90°C and stirred and washed twice, the stirring and washing time is 40min, centrifugal separation is performed to obtain second-washed lithium carbonate, the second-washed lithium carbonate is dried and then air flow pulverized to obtain battery-grade lithium carbonate, and the first washing water is used to prepare a soda ash solution;
[0098] S5, after lithium precipitation, the mother liquor is added with concentrated sulfuric acid for decarbonization, and the pH value at the reaction end point is controlled to be 5.5-6.5. The decarbonized mother liquor is then neutralized with sodium hydroxide, and the pH value at the reaction end point is controlled to be 7.5-8.5. The neutralized mother liquor is concentrated by MVR and then centrifuged to obtain sodium sulfate potassium salt and the concentrated mother liquor. The sodium sulfate potassium salt is returned to S1 for mixing, and the amount of sodium sulfate potassium salt produced is balanced with the amount of sodium sulfate potassium salt used in S1, so as to realize material circulation, and the concentrated mother liquor repeats the operation of S4;
[0099] Take S2 clinker to test the transformation rate and the lithium oxide grade of leached slag. The calculation method of the transformation rate is as follows:
[0100]
[0101] Compared with Example 3, the ratio of sodium potassium sulfate is reduced.
[0102] According to the test, the conversion rate of clinker lithium in the above method is 85.84%, and the total lithium recovery rate is 74.22%.
[0103] Comparative Example 3
[0104] This embodiment provides a method for efficiently and cleanly extracting lithium from low-grade lepidolite, comprising the following steps:
[0105] S1. Fully mix the lithium mica ore with a lithium oxide grade of 1.9% according to the mass ratio of lithium mica: sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz of 100:15:31:4:4:3 to obtain a mixed raw material, and press the mixed raw material into a brick by a hydraulic brick press, and control the compressive strength of the brick to be 24Mpa;
[0106] S2, stacking the bricks of S1, entering the preheating and drying tunnel kiln through the kiln car for drying, transferring to the firing tunnel kiln for high-temperature roasting, controlling the roasting temperature to 950°C, the high-temperature roasting time to 60min, obtaining the burnt clinker, and then cooling in the cooling kiln for crushing, transferring to the vertical mill for grinding, controlling the grinding particle size to -100 mesh to account for 95%, obtaining the fine powder clinker;
[0107] S3. Add the fine powder clinker obtained in S2 into the slag washing filtrate for leaching, control the liquid-solid ratio to 1.3:1, stir and leaching for 30 minutes, filter to obtain the leaching solution, wash the filter residue with circulating water for 2 times, return the slag washing filtrate step by step, and ensure that the lithium oxide content of the leaching solution is 15-20g / L.
[0108] S4, first add lime to the leachate to remove iron, control the pH to 8-9, filter to obtain a primary purified liquid and a primary purified slag; then add soda ash to the primary purified liquid to remove impurities, the added amount is 105-110% of the theoretical value of calcium and magnesium ions in the solution to convert them into calcium carbonate and magnesium carbonate, stir and filter to obtain secondary impurity removal slag and secondary purified liquid; the secondary purified liquid is then concentrated by MVR to a lithium oxide concentration of 28-30g / L to obtain a lithium sulfate concentrate, the concentrate is filtered by resin to deeply remove calcium and magnesium to obtain a purified liquid; the purified liquid Add a soda ash solution to the solution, the amount of soda ash used is 105-115% of the theoretical value of sodium carbonate required to convert all lithium ions in the solution into lithium carbonate, the lithium precipitation reaction temperature is controlled at 95°C, the reaction time is 2h, centrifugal separation is performed to obtain crude lithium carbonate and mother liquor after lithium precipitation, the crude lithium carbonate is then added with pure water at a solid-liquid ratio of 1:4 at 90°C and stirred and washed twice, the stirring and washing time is 40min, centrifugal separation is performed to obtain second-washed lithium carbonate, the second-washed lithium carbonate is dried and then air flow pulverized to obtain battery-grade lithium carbonate, and the first washing water is used to prepare a soda ash solution;
[0109] S5, after lithium precipitation, the mother liquor is added with concentrated sulfuric acid for decarbonization, and the pH value at the reaction end point is controlled to be 5.5-6.5. The decarbonized mother liquor is then neutralized with sodium hydroxide, and the pH value at the reaction end point is controlled to be 7.5-8.5. The neutralized mother liquor is concentrated by MVR and then centrifuged to obtain sodium sulfate potassium salt and the concentrated mother liquor. The sodium sulfate potassium salt is returned to S1 for mixing, and the amount of sodium sulfate potassium salt produced is balanced with the amount of sodium sulfate potassium salt used in S1, so as to realize material circulation, and the concentrated mother liquor repeats the operation of S4;
[0110] Take S2 clinker to test the transformation rate and the lithium oxide grade of leached slag. The calculation method of the transformation rate is as follows:
[0111]
[0112] Compared with Example 4, the calcination time was reduced from 90 min to 60 min.
[0113] According to the test, the conversion rate of clinker lithium in the above method is 86.07%, and the total recovery rate is 75.64%.
[0114] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for efficiently and cleanly extracting lithium from low-grade lepidolite, characterized in that: The following steps are involved: S1: Mixing lepidolite with sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz, and then pressing the mixed raw materials into bricks; S2, stacking, preheating and drying, high-temperature roasting, cooling, crushing and grinding the bricks to obtain fine powder clinker; S3: the fine powder clinker is leached with water, and then a leaching liquid is obtained by solid-liquid separation; S4: The leachate is subjected to impurity removal, concentration, lithium precipitation, and centrifugal separation to obtain crude lithium carbonate and mother liquor after lithium precipitation, and then the crude lithium carbonate is further stirred, washed, dried, and crushed to obtain battery-grade lithium carbonate; S5: The mother liquor after lithium precipitation is decarbonized, neutralized and concentrated to obtain recovered sodium potassium sulfate and concentrated mother liquor, and then the sodium potassium sulfate is recovered and returned to S1 for mixing, and the concentrated mother liquor is returned to S4.
2. A method for efficiently and cleanly extracting lithium from low-grade lepidolite according to claim 1, characterized in that: In S1, the mass ratio of lepidolite to sodium potassium sulfate, calcium sulfate, calcium hydroxide, lime and quartz on a dry basis is 100:(10-15):(30-35):(3-5):(3-5):(2-4).
3. A method for efficiently and cleanly extracting lithium from low-grade lepidolite according to claim 1, characterized in that: In S1: the lithium oxide grade of the lepidolite ore is 1.8-2.0%.
4. The method for efficiently and cleanly extracting lithium from low-grade lepidolite according to claim 1, characterized in that: In the S1, the main content of calcium oxide in the lime is ≥80%, and the main content of silicon dioxide in the quartz is ≥90%.
5. The method for efficiently and cleanly extracting lithium from low-grade lepidolite according to claim 1, characterized in that: In S1: the bricks are pressed into bricks by a hydraulic brick making machine, and the compressive strength of the bricks is 23-25Mpa.
6. The method for efficiently and cleanly extracting lithium from low-grade lepidolite according to claim 1, characterized in that: In S2, the high temperature calcination temperature is 900-950°C, and the calcination time is 60-120 minutes.
7. The method for efficiently and cleanly extracting lithium from low-grade lepidolite according to claim 1, characterized in that: In S2, the particle size of the fine powder clinker is controlled to be above -100 mesh, accounting for more than 95%.
8. The method for efficiently and cleanly extracting lithium from low-grade lepidolite according to claim 1, characterized in that: In S3: water immersion, the liquid-to-solid ratio is controlled to be (1.2-1.5):1, the leaching time is 30-50 minutes, and the leaching temperature is 50°C-80°C.
9. The method for efficiently and cleanly extracting lithium from low-grade lepidolite according to claim 1, characterized in that: In S4: the lithium precipitation reaction temperature is 90-95°C.
10. The method for efficiently and cleanly extracting lithium from low-grade lepidolite according to claim 1, characterized in that: In S5: after lithium precipitation, the mother liquor is decarbonized with sulfuric acid to a pH of 5.5-6.5, and then neutralized with sodium hydroxide to a pH of 7.5-8.5.
Citation Information
Patent Citations
Mica treatment process for preparing lithium carbonate by utilizing lepidolite
CN106636615A
Method for obtaining lithium compound from lepidolite
CN117963952A
Improvements in the recovery of lithium salts from lithium-containing minerals
GB521210A
Carbonatizing roast of lithiumbearing ores
US3380802A